2021
DOI: 10.1192/bjp.2021.129
|View full text |Cite
|
Sign up to set email alerts
|

Building youth and family resilience for better mental health: developing and testing a hybrid model of intervention in low- and middle-income countries

Abstract: Summary Resilience is a dynamic, multi-level, multi-systemic process of positive adaptation at the individual, family and community levels. Promoting resilience can be a cost-effective form of preventive and early intervention, offering significant health advantages for young people throughout their lives. Developing resiliency interventions for youth and their families in low- and middle-income countries (LMICs), particularly in the context of the ongoing pandemic, is especially important given a lack of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…A determinant factor in children’s emotional and behavioral management is parental resilience. Resilience is a dynamic, multi-level, multi-systemic process of positive adaptation (Basu et al, 2022 ) and for these reasons is full in potential. It can be nurtured and strengthened through targeted clinical and social interventions (Basu et al, 2022 ).…”
Section: Implications and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A determinant factor in children’s emotional and behavioral management is parental resilience. Resilience is a dynamic, multi-level, multi-systemic process of positive adaptation (Basu et al, 2022 ) and for these reasons is full in potential. It can be nurtured and strengthened through targeted clinical and social interventions (Basu et al, 2022 ).…”
Section: Implications and Applicationmentioning
confidence: 99%
“…Resilience is a dynamic, multi-level, multi-systemic process of positive adaptation (Basu et al, 2022 ) and for these reasons is full in potential. It can be nurtured and strengthened through targeted clinical and social interventions (Basu et al, 2022 ). Study 1 slso showed the importance of reducing parental distress.…”
Section: Implications and Applicationmentioning
confidence: 99%
“…The World Health Organization (2014) considered different models through which mental health provision can be integrated in MWC, of which the stepped-care approach was more compatible with the service framework adopted in this study. This also took into consideration the contextual characteristics of MWC, in extending the model to families, schools and communities; and co-producing solutions with local stakeholders to account for inequalities and sociocultural factors (Basu et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these barriers, efforts have been made to expand key resources—such as trauma-informed cognitive-behavioral therapy—into low-income communities [ 68 ], such as the Elijah Cummings Healing City Baltimore Act in Baltimore City, MD [ 69 ]. Furthermore, in low-income settings, it may be that hybrid models targeting children and their families with “options to engage through communities, schools, and the family unit” may be promising [ 70 ]. Ultimately, while cardiovascular health education is critical, systemic change that promotes equitable access to health resources that can stem the tide of cardiovascular disease remains a priority.…”
Section: Discussionmentioning
confidence: 99%